Effect of Tomato Juice in Tris-Yolk-Citrate Extender on Refrigeration Preservation of Cauda Epididymal Spermatozoa of Buck - Chaudhary, LM; Khasatiya, CT; Amarjeet; Yede, AB (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was carried out on the preservation of epididymal spermatozoa of buck at refrigerated temperature without and with tomato juice as a supplement in Tris egg yolk citrate extender. The eight pairs of testicles including epididymis (total 16) from slaughtered bucks were collected within 2–4 hours of their slaughter. Sperms collected from cauda epididymis were preserved at refrigerated temperature up to 48 hours in tris egg yolk citrate extender at 300 million sperm/mL with different concentration of tomato juice (0%, 4%, 6%, 8%, and 10%) and the physical characteristics of spermatozoa were assessed to know the effect of tomato juice (Tj). The mean dead, abnormal and HOST non-reacted spermatozoa increased significantly (p <0.05) at every 12-hour intervals of preservation in the dilutor without and with different concentration of tomato juice. Tomato juice exerted an adverse effect on physical characteristics of sperm during refrigeration preservation. All the three sperm traits studied however revealed significant (p <0.01) positive interrelationships with correlations of 0.31 to 0.72.